Pengaruh Promosi Dan Harga Terhadap Keputusan Pembelian Dengan Labelisasi Halal Sebagai Variabel Intervening (Studi Pada Konsumen Home Industri Bakso Kembar Kota Metro) - Selamet Fuadi; Sugeng; Nurul Aeni (Universitas Muhammadiyah Metro, 2025)
Purchasing decisions from consumers regarding the products they produce is something thatis of concern to every business person in formulating a strong marketing strategy in order tomaximize profits, create consumer satisfaction and be able to compete with businesses. Thereis a problem at the location of the object of my research, namely the decline in decisions.purchases caused by promotions and selling prices compared to competitors resulted in adecrease in consumers and made consumers consider purchasing decisions at the BaksoKembar Home Industry in Metro City. This research aims to find out whether promotionsinfluence halal labeling, to find out whether price influences halal labeling, to find outwhether promotions influence purchasing decisions, to find out whether price influencespurchasing decisions, to find out whether halal labeling influences purchasing decisions.This research uses quantitative research, taking a sample of 57 Bakso Kembar Metro Cityconsumers. Data collection uses the questionnaire method and data analysis uses ValidityTest, Reliability Test, Normality Test, Homogeneity Test, Linearity Test and Variable Regression Analysis using the program (SPSS 22). The results of the research show that thereis a direct influence between Promotion on Halal Labeling, There is a direct influencebetween Price on Halal Labeling, There is a direct influence between Promotion onPurchasing Decisions, There is a direct influence between Price on Purchasing Decisions,There is a direct influence between Labeling Halal on Purchasing Decisions